2003
DOI: 10.1108/02635570310480015
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual model of supply chain flexibility

Abstract: This paper presents an integrated conceptual model of supply chain flexibility. It examines flexibility classification schemes and the commonalities of flexibility typologies published in the literature to create a theoretical foundation for analyzing the components of supply chain flexibility. Even though there has been a tremendous amount of research on the topic of flexibility, most of it has been confined to intra‐firm flexibility concerns. As supply chain management goes beyond a firm’s boundaries, the fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
283
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 389 publications
(306 citation statements)
references
References 25 publications
(34 reference statements)
8
283
0
5
Order By: Relevance
“…The result of this research has also confirmed the propositions of theoretical studies (Duclos et al, 2003;Vinod Kumar et al, 2006), which ISSN 1941-899X 2013 states that anticipating uncertainties in a supply chain is the primary concern for determining SCF. This is different from the findings of Angel & Manuela (2005) that SCF has significant impact in improving company performance.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The result of this research has also confirmed the propositions of theoretical studies (Duclos et al, 2003;Vinod Kumar et al, 2006), which ISSN 1941-899X 2013 states that anticipating uncertainties in a supply chain is the primary concern for determining SCF. This is different from the findings of Angel & Manuela (2005) that SCF has significant impact in improving company performance.…”
Section: Discussionsupporting
confidence: 77%
“…SCF should be approached in an integrated manner and oriented towards customers. Duclos et al (2003) states that literature review on flexibility still have some weaknesses in discussing the cross-functional and cross-business nature of SCF.…”
Section: Supply Chain Flexibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly though, rapid and ongoing change is surpassed by the rate of failure. Customers are demanding more variety, better quality and service including both reliability and faster delivery [33]. Reduction in the number of EPMs has resulted in some advantages for both customers and suppliers.…”
Section: E-procurement Marketplacementioning
confidence: 99%
“…Vokurka and O'LearyKelly [105] expanded different dimensions developed by Browne et al [16] and Sethi and Sethi [88] on manufacturing flexibility to fifteen elements (machine; material handling; operations; automation; labor; process; routing; product; new design; delivery; volume; expansion; program; production and market). The main six components of supply chain flexibility indicated by Duclos et al [33] are operations systems flexibility, market flexibility, supply flexibility, logistics flexibility, organizational flexibility and information system flexibility. He also proposed the framework for supply chain flexibility based on these dimensions.…”
Section: Flexibilitymentioning
confidence: 99%